2021
DOI: 10.1097/hnp.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Therapies Used by Indonesians With Myocardial Infarction

Abstract: This descriptive, cross-sectional study was conducted to identify types, frequency, methods, duration, and purpose of complementary therapies used by Indonesians with myocardial infarction. The majority of the respondents used biologically based therapies, with the most common subtype being herbs. The purpose of using biologically based therapies was for health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Edukasi tentang PJK telah diberikan menggunakan buku pedoman home care lansia penderita PJK, mendapatkan respon yang penuh antusias dari para lansia. Lansia mengungkapkan mereka mendapatkan informasi kesehatan yang bermanfaat untuk memanajemen kesehatan jantungnya dengan life style yang perlu dirubah dan dijaga konsisten, sehingga mengurangi peningkatan kolesterol yang berpotensi menyebabkan penyumbatan pembuluh darah (Malakar et al, 2019;Muflihah et al, 2021).…”
Section: Pembahasanunclassified
“…Edukasi tentang PJK telah diberikan menggunakan buku pedoman home care lansia penderita PJK, mendapatkan respon yang penuh antusias dari para lansia. Lansia mengungkapkan mereka mendapatkan informasi kesehatan yang bermanfaat untuk memanajemen kesehatan jantungnya dengan life style yang perlu dirubah dan dijaga konsisten, sehingga mengurangi peningkatan kolesterol yang berpotensi menyebabkan penyumbatan pembuluh darah (Malakar et al, 2019;Muflihah et al, 2021).…”
Section: Pembahasanunclassified
“…In the United States alone adults aged >20 from 2011 to 2014, reaching 7.900,000 (3.0%) had myocardial infarction. (5) Based on data it has been found that the incidence of myocardial infarction has increased, namely in young adults. (6) While South Asians themselves represent about a quarter of the world's population with a very young age, namely younger than 35 years.…”
Section: Introductionmentioning
confidence: 99%